operational risk of commercial banks in China and analysis of its major influencing factors: Evidence from eighteen commercial banks - Du, Muzi (2022)
This dissertation seeks to measure the operational risk level of Chinese commercial banks and explore its major influencing factors from the standpoint of bank characteristics and operational risk management. The absolute and relative value of the operational risk was calculated from 3 perspectives: the overall level of Chinese commercial banks, the level of the three ownership structure types of banks, and the level of each individual bank. The study found that Chinese commercial banks' overall risk management status is good. This study also found that the ownership structure affects the level of operational risk. Among the three forms of banks' ownership structures, the state-owned banks have the best ability to manage operational risk. The empirical findings showed that the growth rate of asset scale, the amount of money invested in managing operational risk and the proportion of the increase of salary of employees in the increase of asset of banks are the major factors influencing the level of operational risk that the bank faces. In addition, the bank faces more risk if it belongs to urban commercial banks. Moreover, from the perspective of the relative value of operational risk, the growth rate of asset scale, the proportion of increment of operational risk management input in increment of asset, and the shareholding concentration are the main factors influencing the banks' ability for operational risk management.